GERIATRIC GYMNASTIC TO QUALITY OF SLEEP IN PTSW SENJARAWI BANDUNG - Meilirianta Meilirianta; Maspupah Maspupah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Elderly has decreased in many body system including the impact on sleep disorder. The purpose of this study was to analize effect of geriatric gymnastic on sleep quality of the elderly. Methods. This research used quasy experiment methods with pre and post test only non equivalent control group design. The population in this study was the elderly as many as 82 people. Sample in this research was 30 participants that are defi ned with total sampling method who was appropriated with the criteria. Sampel was devided into two groups which are 15 people of intervention group and 15 people of control group. Data instrument in measuring the quality of sleep used PSQI (Pittsburgh Sleep Quality Index) by observation. Result. There was a signifi cant effect of geriatric gymnasticon sleep quality of the elderly at Tresna Werdha Senjarawi Social Home Bandung with t-test, p-value 0.000 or < 0.05. Discussion. The geriatric gymnastics can be designed more interest the elderly to follow this activities regulary so can overcome sleep disorders in the elderly.Keywords : Quality of Sleep, Geriatric Gymnastic, Elderly